Evaluasi Kepatuhan POS Pembelian Perusahaan Tekstil dalam Persiapan Sertifikasi ISO 9001:2015 - Jesica Handoko; Ceicilia Bintang Hari Yudhanti; Bernadetta Diana Nugraheni; Tineke Wehartaty Wehartaty (Politeknik Caltex Riau, 2023)
The research object is PT Jimas, a textile waste processing manufacturing company, where PT Jimas is in preparation for ISO 9001:2015 certification. During the COVID 19 pandemic, PT Jimas remained fully operational in accordance with government regulations and underwent changes in procedures and documents in its purchasing cycle. One of the things assessed in ISO 9001: 2015 certification is compliance with the implementation of existing SOPs. Purchasing cycle SOP compliance audit, manufacturing companies can check the conformity of the management system with the audit criteria, namely the required material standards, the company's purchasing management system, supplier requirements and others. This research is expected to contribute to PT Jimas, especially in measuring compliance in the implementation of the purchase cycle SOP, by designing a Purchase Cycle Compliance checklist, starting from the initial supplier selection procedure to paying purchase debts.The research was conducted using descriptive qualitative methods, namely interviews and checking related documents. The results of this study are that PT Jimas is quite compliant in carrying out procedures and using purchasing documents, but in the context of adjusting to changes related to the COVID 19 pandemic, PT Jimas requires socialization of the latest SOP purchasing cycle. The socialization of the implementation of the SOP purchasing cycle is expected to increase PT Jimas' compliance and be useful in preparation for obtaining ISO 9001: 2015 certification.